2011
DOI: 10.1007/s13361-010-0037-0
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Control of Protonation in Electrospray Ionization

Abstract: The site of protonation in a molecule can greatly affect the fragments observed in product ion MS/MS spectra. In electrospray positive ionization mass spectra, protonation usually occurs predominantly on the most basic site on the molecule to produce the thermodynamically favored protonated species. However, the literature is unclear whether liquid phase or gas phase thermodynamics has the greater influence. This paper describes the protonation and fragmentation behavior of crizotinib and two of its impurities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 24 publications
1
59
0
Order By: Relevance
“…These indicate that [2 (D)+D] + at m/z 191 was different from the m/z 191 ion from [Trp (D)+D] + . Protonation sites lead to their fragmentation difference [21][22][23]. The proton of protonated compound 2 lay on the N atom more easily [24,25], and then migrated via 1,5-hydrogen migration (Scheme 1(b)) and lost a CHDCO.…”
Section: For the Collision-induced Dissociation (Cid)-ms/ms Analysis mentioning
confidence: 99%
“…These indicate that [2 (D)+D] + at m/z 191 was different from the m/z 191 ion from [Trp (D)+D] + . Protonation sites lead to their fragmentation difference [21][22][23]. The proton of protonated compound 2 lay on the N atom more easily [24,25], and then migrated via 1,5-hydrogen migration (Scheme 1(b)) and lost a CHDCO.…”
Section: For the Collision-induced Dissociation (Cid)-ms/ms Analysis mentioning
confidence: 99%
“…For example, with pentaglycine acid, ΔH f for the peptide ion deprotonated at the C-terminal carboxylic acid group is -325.2 kcal/mol, which is more favorable than ΔH f 's for the ions deprotonated at the central amide nitrogen (-312.8 kcal/mol) and at the penultimate amide nitrogen (-298.7 kcal/mol). ESI is a very soft ionization technique that produces ions will little excess energy and, therefore, preferentially generates ions with the lowest energy structure [63][64][65][66][67]. As a result, the majority of the precursor ions produced by ESI on the peptide acids should be deprotonated at the C-terminal carboxylic acid group.…”
Section: Peptide Deprotonation Sitementioning
confidence: 99%
“…Their work demonstrated an unpredictable effect on the efficacy and no effect on the selectivity of the peptides studied. Krstenansky et al [22] synthesized several Cterminal analogs of hirudin (54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65) to probe the structureactivity relationship. The C-terminal amide was among the modifications studied and its presence lessened the activity of the antithrombin peptide.…”
Section: Introductionmentioning
confidence: 99%
“…has been raised by Kass et al [19][20][21][22][23][24][25][26][27][28][29]. Generally, we know that protonation occurs predominantly on the most basic site of the molecule to generate the thermodynamically favored protonated ions in ESI.…”
Section: Introductionmentioning
confidence: 99%
“…We also revealed that the protonation site of the [M + H] + ion of p-(dimethylamino)chalcone produced by atmospheric pressure chemical ionization (APCI) could differ on the basis of the solvent system and operation condition [28]. Joyce and Richards reported the kinetic control of protonation process in ESI by reference to the MS and MS/ MS spectra of crizotinib and two related impurities because of steric hindrance at the most basic site [29]. These compounds contain two possible protonation sites, a pyridine nitrogen and a piperidine nitrogen (a secondary amine) and the piperidine nitrogen is the preferred site of protonation for crizotinib itself.…”
Section: Introductionmentioning
confidence: 99%